Prevalence of chronic cough and possible causes in the general population based on the Korean National Health and Nutrition Examination Survey. Issue 37 (September 2016) - Koo, Hyeon-Kyoung; Jeong, Ina; Lee, Sei Won; Park, Jinkyeong; Kim, Joo-Hee; Park, So Young; Park, Hye Yun; Rhee, Chin Kook; Kim, Yee Hyung; Jung, Ji Ye; Kim, Sung-Kyoung; Kim, Yong Hyun; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although chronic cough is very common, its prevalence and causes have been rarely reported in the large general population including smokers. This study aimed to identify the prevalence of possible causes of chronic cough and their clinical impact. From Korean National Health and Nutrition Examination Survey (KNHANES) data including 119, 280 adults aged over 40 years, 302 individuals with chronic cough were recruited irrespective of smoking status. Data from questionnaire, laboratory tests including spirometry, chest radiographs, and otorhinolaryngologic examination were analyzed. The prevalence of chronic cough in adults was 2.5% ± 0.2%. Current smokers occupied 47.7% ± 3.8% of study population and 46.8% ± 3.9% of the subjects showed upper airway cough syndrome (UACS). Based on spirometry, chronic obstructive pulmonary disease (COPD) was identified in 26.4% ± 3.5%. Asthma explained for 14.5% ± 2.8% of chronic cough. Only 4.1% ± 1.6% showed chronic laryngitis suggesting gastro-esophageal reflux-related cough. Abnormalities on chest radiography were found in 4.0% ± 1.2%. Interestingly, 50.3% ± 4.5% of study subjects had coexisting causes. In multivariate analysis, only current smoking (odds ratio [OR] 3.16, P  < 0.001), UACS (OR 2.50, P  < 0.001), COPD (OR 2.41, P  < 0.001), asthma (OR 8.89, P  < 0.001), and chest radiographic abnormalities (OR 2.74, P  = 0.003) were independent risk factor for chronic cough. This pattern was not different according to smoking status excepting the prevalence of COPD. Smoking, COPD, and chest radiographic abnormalities should be considered as causes of chronic cough, along with UACS and asthma. Gastro-esophageal reflux-related cough is not prevalent in study population.